Natural compounds targeting mitochondrial dysfunction: emerging therapeutics for target organ damage in hypertension - Liao, Xiaolin; Han, Yuanshan; He, Ying; Liu, Jianjun; Wang, Yuhong (Frontiers in Pharmacology, 2023)
Hypertension generally causes target organ damage (TOD) in the heart, brain, kidney, and blood vessels. This can result in atherosclerosis, plaque formation, cardiovascular and cerebrovascular events, and renal failure. Recent studies have indicated that mitochondrial dysfunction is crucial in hypertensive TOD. Consequently, mitochondria-targeted therapies attract increasing attention. Natural compounds are valuable resources for drug discovery and development. Many studies have demonstrated that natural compounds can ameliorate mitochondrial dysfunction in hypertensive TOD. This review examines the contribution of mitochondrial dysfunction to the development of TOD in hypertension. Moreover, it summarizes therapeutic strategies based on natural compounds that target mitochondrial dysfunction, which may be beneficial for preventing and treating hypertensive TOD.